Customer satisfaction in Slovak spas: Case studies of Rajecké Teplice, Piešťany and Brusno - Čuka, Peter; Gregorová, Bohuslava (Turyzm/Tourism, 2020)
This work aims to present a customer satisfaction model using selected examples from the spa industry. Specifically, it is a presentation of the satisfaction of spa customers and visitors to the Slovak spa of Rajecké Teplice, in comparison with Piešťany and Brusno. Customer satisfaction is a multiple phenomenon which is evaluated mainly by qualitative methods. Our motivation is to draw attention to the difficulty and subjectivity of qualitative research concerning such satisfaction, especially at in-service facilities in selected Slovak spas. Customers ranked them and created a ‘top 12’, according to their importance in the subjective perception of spa environments, services, health services and attractions in terms of satisfaction. In addition, the result is a comparison of the individual satisfaction of spa customers in heterogeneous spa towns. Piešťany is the most important Slovak spa center, Trenčianske Teplice is a medium-sized spa town, and Brusno a small stagnant spa.